Staphylinidae (Insecta: Coleoptera) in Latin America: synopsis, annotated catalog, diversity and distribution - Asenjo, Angélico; Klimaszewski, Jan; Chandler, Donald S.; Fierros-López, Hugo Eduardo; Vieira, Juliana S. (Zootaxa, 2019)
The taxonomic diversity of species and genera of Staphylinidae and their distribution in Latin America are discussed and listed/tabulated based on published literature. In total, 11,675 species in 1075 genera are reported from Latin America. South America has the most recorded species for Latin America, 7773 including 7079 endemic species. The four subfamilies with the highest total number of genera including endemic genera are Aleocharinae, Staphylininae, Pselaphinae, and Paederinae. All recorded genera and their synonyms are listed alphabetically within the subfamilies of Staphylinidae, providing a catalog of published genera for Latin America. Two hundred forty-four color or black and white images of species representing different genera are provided.